Causes of Treatment Failure in Children With Inflammatory Bowel Disease Treated With Infliximab: A Pharmacokinetic Study. - Naviglio, Samuele; Lacorte, Doriana; Lucafò, Marianna; Cifù, Adriana; Favretto, Diego; Cuzzoni, Eva; Silvestri, Tania; Pozzi Mucelli, Martina; Radillo, Oriano; Decorti, Giuliana; Fabris, Martina; Bramuzzo, Matteo; et al. (J Pediatr Gastroenterol Nutr, 2019)
OBJECTIVES: Anti-tumor necrosis factor antibodies have led to a revolution in the treatment of inflammatory bowel diseases (IBD); however, a sizable proportion of patients does not respond to therapy. There is increasing evidence suggesting that treatment failure may be classified as mechanistic (pharmacodynamic), pharmacokinetic, or immune-mediated. Data regarding the contribution of these factors in children with IBD treated with infliximab (IFX) are still incomplete. The aim was to assess the causes of treatment failure in a prospective cohort of pediatric patients treated with IFX. METHODS: This observational study considered 49 pediatric (median age 14.4) IBD patients (34 Crohn disease, 15 ulcerative colitis) treated with IFX. Serum samples were collected at 6, 14, 22 and 54 weeks, before IFX infusions. IFX and anti-infliximab antibodies (AIA) were measured using enzyme linked immunosorbent assays. Disease activity was determined by Pediatric Crohn's Disease Activity Index or Pediatric Ulcerative Colitis Activity Index. RESULTS: Clinical remission, defined as a clinical score <10, was obtained by 76.3% of patients at week 14 and by 73.9% at week 54. Median trough IFX concentration was higher at all time points in patients achieving sustained clinical remission. IFX levels during maintenance correlated also with C-reactive protein, albumin, and fecal calprotectin. After multivariate analysis, IFX concentration at week 14 >3.11 μg/mL emerged as the strongest predictor of sustained clinical remission. AIA concentrations were correlated inversely with IFX concentrations and directly with adverse reactions. CONCLUSIONS: Most cases of therapeutic failure were associated with low serum drug levels. IFX trough levels at the end of induction are associated with sustained long-term response.

Does the Application of Heat Gel Pack After Eutectic Mixture of Local Anesthetic Cream Improve Venipuncture or Intravenous Cannulation Success Rate in Children? A Randomized Control Trial. - Schreiber, Silvana; Cozzi, Giorgio; Patti, Giuseppa; Taddio, Andrea; Montico, Marcella; Pierobon, Chiara; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVE: Needle-related procedures are the most common sources of pain for children in the hospital setting. The most used topical anesthetic, eutectic mixture of local anesthetic (EMLA) cream, may cause transient vasoconstriction. It has been postulated that this vasoconstriction may decrease vein visualization. The application of heat gel pack after removal of EMLA cream in the site of venipuncture counteracts the vasoconstriction, improving vein visualization. We assessed using a prospective randomized controlled trial whether the application of heat gel pack increases the needle procedure success rate. The primary study outcome was procedural success rate at the first attempt. METHODS: The study enrolled 400 children, 200 of whom applied heat gel pack after removing EMLA (treatment group) and 200 did not (control group). Procedural success rate at the first attempt, vein perception before procedure, procedural pain, and adverse events were recorded in both groups. RESULTS: Eighty-eight percent of the procedures were successful at the first attempt in the treatment group and 89% in the control group (P = 0.876). Vein perception was not significantly different in the 2 groups (P = 0.081). Pain score after the procedure was similar in the 2 groups. CONCLUSIONS: This study shows that the application of heat gel pack after removal of EMLA cream does not improve venipuncture or intravenous cannulation success rate.
Keywords: Anesthetics, Local; Child; Child, Preschool; Female; Hot Temperature; Humans; Lidocaine; Lidocaine, Prilocaine Drug Combination; Male; Pain; Pain Management; Phlebotomy; Prilocaine; Prospective Studies

Fecal Calprotectin to Detect Inflammatory Bowel Disease in Juvenile Idiopathic Arthritis. - Ferrara, Giovanna; Pastore, Serena; Sancin, Lara; Torelli, Lucio; Radillo, Oriano; Bramuzzo, Matteo; Bibalo, Chiara; Tommasini, Alberto; Ventura, Alessandro; Taddio, Andrea (J Rheumatol, 2018)
OBJECTIVE: This study aimed to test fecal calprotectin (FC) as a screening tool to identify inflammatory bowel disease (IBD) among patients with juvenile idiopathic arthritis (JIA). METHODS: FC level < 100 g/kg was considered normal. Patients with 2 consecutive FC dosage ≥ 100 g/kg underwent endoscopic evaluation. RESULTS: There were 113 patients with JIA enrolled. FC was raised in 7 patients out of 113. All patients had IBD. In 3/7 patients, high FC levels were the only sign consistent with IBD. CONCLUSION: FC is a useful, economical, and noninvasive diagnostic tool to identify JIA patients with underlying IBD.

Flares After Withdrawal of Biologic Therapies in Juvenile Idiopathic Arthritis: Clinical and Laboratory Correlates of Remission Duration. - Simonini, Gabriele; Ferrara, Giovanna; Pontikaki, Irene; Scoccimarro, Erika; Giani, Teresa; Taddio, Andrea; Meroni, Pier Luigi; Cimaz, Rolando (Arthritis Care Res (Hoboken), 2018)
OBJECTIVE: To assess the time in remission after discontinuing biologic therapy in patients with juvenile idiopathic arthritis (JIA). METHODS: We enrolled 135 patients followed in 3 tertiary-care centers. The primary outcome was to assess, once remission was achieved, the time in remission up to the first flare after discontinuing treatment. Mann-Whitney U test, Wilcoxon's signed rank test for paired samples, chi-square tests, and Fisher's exact test were used to compare data. Pearson's and Spearman's correlation tests were used to determine correlation coefficients for different variables. To identify predictors of outcome, Cox regression model and Kaplan-Meier curves were constructed, each one at the mean of entered covariates. RESULTS: The majority of enrolled patients flared after stopping treatment with biologics (102 of 135, 75.6%) after a median followup time in remission off therapy of 6 months (range 3-109 months). A higher probability of maintaining remission after discontinuing treatment was present in systemic-onset disease compared to the rest of the JIA patients (Mantel-Cox χ = 8.31, P < 0.004). In analysis limited to children with JIA with polyarticular and oligoarticular disease, patients who received biologics >2 years after achieving remission had a higher probability of maintaining such remission off therapy (mean ± SD 18.64 ± 3.3 months versus 11.51 ± 2.7 months [P < 0.009]; Mantel-Cox χ = 9.06, P < 0.002). No other clinical variable was significantly associated with a long-lasting remission. CONCLUSION: Children with oligoarticular and polyarticular JIA who stop treatment before 2 years from remission have a higher chance of relapsing after biologic withdrawal.

Describing Kawasaki shock syndrome: results from a retrospective study and literature review. - Taddio, Andrea; Rossi, Eleonora Dei; Monasta, Lorenzo; Pastore, Serena; Tommasini, Alberto; Lepore, Loredana; Bronzetti, Gabriele; Marrani, Edoardo; Mottolese, Biancamaria D'Agata; Simonini, Gabriele; Cimaz, Rolando; Ventura, Alessandro (Clin Rheumatol, 2017)
Kawasaki shock syndrome (KSS) is a rare manifestation of Kawasaki disease (KD) characterized by systolic hypotension or clinical signs of poor perfusion. The objectives of the study are to describe the main clinical presentation, echocardiographic, and laboratory findings, as well as the treatment options and clinical outcomes of KSS patients when compared with KD patients. This is a retrospective study. All children referred to two pediatric rheumatology units from January 1, 2012, to December 31, 2014, were enrolled. Patients were divided into patients with or without KSS. We compared the two groups according to the following variables: sex, age, type of KD (classic, with less frequent manifestations, or incomplete), clinical manifestations, cardiac involvement, laboratory findings, therapy administered, response to treatment, and outcome. Eighty-four patients with KD were enrolled. Of these, five (6 %) met the criteria for KSS. Patients with KSS had higher values of C-reactive protein (p = 0.005), lower hemoglobin levels (p = 0.003); more frequent hyponatremia (p = 0.004), hypoalbuminemia (p = 0.004), and coagulopathy (p = 0.003); and increase in cardiac troponins (p = 0.000). Among the KSS patients, three had a coronary artery involvement, but none developed a permanent aneurysm. Intravenous immunoglobulin resistance was more frequent in the KSS group, although not significantly so (3/5, 60 % vs. 23/79, 30 %, P = NS). None of the five cases was fatal, and all recovered without sequelae. KSS patients are more likely to have higher rates of cardiac involvement. However, most cardiovascular abnormalities resolved promptly with therapy.
Keywords: C-Reactive Protein; Child; Child, Preschool; Echocardiography; Female; Heart Failure; Hemoglobins; Humans; Immunoglobulins, Intravenous; Male; Mucocutaneous Lymph Node Syndrome; Retrospective Studies; Shock; Syndrome

Predictors of Relapse after Discontinuing Systemic Treatment in Childhood Autoimmune Chronic Uveitis. - Simonini, Gabriele; Bracaglia, Claudia; Cattalini, Marco; Taddio, Andrea; Brambilla, Alice; de Libero, Cinzia; Pires Marafon, Denise; Caputo, Roberto; Cimaz, Rolando (J Rheumatol, 2017)
OBJECTIVE: To identify clinical predictors of relapse in childhood autoimmune chronic uveitis after stopping systemic treatment. METHODS: A retrospective, multicenter, cohort study. RESULTS: Ninety-four children in remission, receiving no treatments and with at least a 6-month followup, were enrolled. A higher probability of maintaining remission after discontinuing treatment was shown in idiopathic compared with juvenile idiopathic arthritis uveitis (Mantel-Cox chi-square = 23.21) if inactivity had been obtained within 6 months from starting systemic treatment (Mantel-Cox chi-square = 24.17) and by antitumor necrosis factor-α treatment (Mantel-Cox chi-square = 6.43). CONCLUSION: Type of disease, time, and type of systemic therapy to achieve inactivity predict different duration of uveitis remission after treatment withdrawal.
Keywords: Adolescent; Antirheumatic Agents; Autoimmune Diseases; Child; Child, Preschool; Female; Humans; Male; Predictive Value of Tests; Recurrence; Retrospective Studies; Treatment Outcome; Uveitis; Withholding Treatment

A premenarcheal girl with urogenital bleeding. - Lora, Angela; Scrimin, Federica; Taddio, Andrea; Ventura, Alessandro; Barbi, Egidio (Arch Dis Child, 2017)

An Update on the Pathogenesis and Treatment of Chronic Recurrent Multifocal Osteomyelitis in Children. - Taddio, Andrea; Zennaro, Floriana; Pastore, Serena; Cimaz, Rolando (Paediatr Drugs, 2017)
Chronic recurrent multifocal osteomyelitis (CRMO), also known as chronic non-bacterial osteomyelitis (CNO), is a rare inflammatory disorder that primarily affects children. It is characterized by pain, local bone expansion, and radiological findings suggestive of osteomyelitis, usually at multiple sites. CRMO predominantly affects the metaphyses of long bones, but involvement of the clavicle or mandible are suggestive of the diagnosis. CRMO is a diagnosis of exclusion, and its pathogenesis remains unknown. Differential diagnosis includes infection, malignancies, benign bone tumors, metabolic disorders, and other autoinflammatory disorders. Biopsy of the bone lesion is not often required but could be necessary in unclear cases, especially for differentiation from bone neoplasia. Non-steroidal anti-inflammatory drugs (NSAIDs) are the first-line treatment. Alternative therapies have been used, including corticosteroids, methotrexate, bisphosphonates, and tumor necrosis factor (TNF)-α inhibitors. No guidelines have been established regarding diagnosis and treatment options. This manuscript gives an overview of the most recent findings on the pathogenesis of CRMO and clinical approaches for patients with the condition.
Keywords: Adrenal Cortex Hormones; Anti-Inflammatory Agents, Non-Steroidal; Child; Chronic Disease; Diagnosis, Differential; Humans; Osteomyelitis; Recurrence; Tumor Necrosis Factor-alpha

Acute lobar nephritis in children: Not so easy to recognize and manage. - Bibalo, Cristina; Apicella, Andrea; Guastalla, Veronica; Marzuillo, Pierluigi; Zennaro, Floriana; Tringali, Carmela; Taddio, Andrea; Germani, Claudio; Barbi, Egidio (World J Clin Pediatr, 2016)
Acute lobar nephritis (ALN) is a localized non-liquefactive inflammatory renal bacterial infection, which typically involves one or more lobes. ALN is considered to be a midpoint in the spectrum of upper urinary tract infection, a spectrum ranging from uncomplicated pyelonephritis to intrarenal abscess. This condition may be difficult to recognize due to the lack of specific symptoms and laboratory findings. Therefore the disease is probably underdiagnosed. Computed tomography scanning represents the diagnostic gold standard for ALN, but magnetic resonance imagine could be considered in order to limit irradiation. The diagnosis is relevant since initial intravenous antibiotic therapy and overall length of treatment should not be shorter than 3 wk. We review the literature and analyze the ALN clinical presentation starting from four cases with the aim to give to the clinicians the elements to suspect and recognize the ALN in children.

A Child with Severe Developmental Delay and Growth Retardation. - Rossetto, Elena; Matarazzo, Lorenza; Maschio, Massimo; Taddio, Andrea; Costa, Paola; Ventura, Alessandro (J Pediatr, 2016)

Chronic nonbacterial osteomyelitis may be associated with renal disease and bisphosphonates are a good option for the majority of patients. - Pastore, Serena; Ferrara, Giovanna; Monasta, Lorenzo; Meini, Antonella; Cattalini, Marco; Martino, Silvana; Alessio, Maria; La Torre, Francesco; Teruzzi, Barbara; Gerloni, Valeria; Breda, Luciana; Taddio, Andrea; et al. (Acta Paediatr, 2016)
AIM: The aim of this Italian study was to describe the clinical features, treatment options and outcomes of a cohort of patients with chronic nonbacterial osteomyelitis (CNO). METHODS: This was a retrospective cohort study. Laboratory data, diagnostic imaging, histological features and clinical course are reported. RESULTS: We enrolled 47 patients diagnosed with CNO. Bone pain was the leading symptom, and multifocal disease was present in 87% of the patients. The majority of the bone lesions were located in the appendicular skeleton (58%). Extraosseous manifestations were present in 34% of the patients, and renal involvement was detected in four patients. Inflammatory indices were increased in 80%, and bone x-rays were negative in 15% of the patients. Nonsteroidal anti-inflammatory drugs (NSAIDs) were the first therapy for all patients, achieving clinical remission in 27%. A good response to NSAIDs was significantly associated with a better prognosis. Bisphosphonates were used in 26 patients, with remission in 73%. Only six patients (13%), all with spine involvement, developed sequelae. CONCLUSION: We found a possible association between CNO and renal disease. Bisphosphonates were more likely to lead to clinical remission when NSAIDs and corticosteroids had failed. Vertebral localisation was the only risk factor for potential sequelae.

The Great Pretender: Pediatric Wandering Spleen: Two Case Reports and Review of the Literature. - Radillo, Lucia; Taddio, Andrea; Ghirardo, Sergio; Bramuzzo, Matteo; Pederiva, Federica; Maschio, Massimo; Barbi, Egidio (Pediatr Emerg Care, 2016)
Wandering spleen is a rare condition, typically not only due to embryological defects of the splenic ligaments, but also secondary to trauma and splenomegaly. The most common presentation is acute abdomen with a mobile abdominal mass or recurrent abdominal pain. However, the spleen may be temporary in its normal position, and patients could be asymptomatic. A familiarity, if present, strengthens the diagnostic suspect.Abdominal ultrasonography and computed tomography are the examination of choice, and the management is surgical.

A minor trauma revealing linear morphoea in a 4-year-old female. - Pastore, Serena; Contorno, Sarah; Caddeo, Giulia; Calligaris, Lorenzo; Taddio, Andrea (Arch Dis Child, 2016)

A quasi randomized-controlled trial to evaluate the effectiveness of clowntherapy on children's anxiety and pain levels in emergency department. - Felluga, Margherita; Rabach, Ingrid; Minute, Marta; Montico, Marcella; Giorgi, Rita; Lonciari, Isabella; Taddio, Andrea; Barbi, Egidio (Eur J Pediatr, 2016)
UNLABELLED: The aim of the study is to investigate if the presence of medical clowns during painful procedures in the emergency department (ED) affects children's anxiety and pain. Forty children (4-11 years) admitted to the ED with the need of painful procedures were prospectively enrolled. They were randomly assigned to the clown group, where children interacted with clowns or to the control group in which they were entertained by parents and ED nurses. The children's anxiety was assessed by the Children's Anxiety and Pain Scales; pain was evaluated with the Numerical Rating Scale and Wong-Backer Scale, according to the children's age. Staff and clown's opinions were evaluated by means of dedicated questionnaires. Children's anxiety levels in the clown group were significantly lower than those compared with the control group, while children's pain levels did not change between the two groups. CONCLUSION: The presence of clowns in the ED before and during painful procedures was effective in reducing children's anxiety. WHAT IS KNOWN: • Anxiety and fear caused by medical procedures exacerbate children's pain and may interfere with the procedure. • To reduce anxiety, fear, and pain and to facilitate patient's evaluation, different non-pharmacological approaches have been proposed and positive effects of laughter and humor have been reported. What is New: • The presence of clowns in the waiting room and in the ED during medical evaluation and painful procedures helps to reduce children's anxiety.

Recent advances in the use of Anti-TNFα therapy for the treatment of juvenile idiopathic arthritis. - Taddio, Andrea; Cattalini, Marco; Simonini, Gabriele; Cimaz, Rolando (Expert Rev Clin Immunol, 2016)
Juvenile Idiopathic Arthritis (JIA) encompasses a group of diseases of unknown etiology having in common arthritis in at least 1 joint that persists for 6 weeks and begins before 16 years of age, with other conditions excluded. With a prevalence of 1 per 1,000 children in the USA, JIA is the most common pediatric rheumatic illness and a major cause of acquired childhood disability. During the last 20 years, the advent of host immune response modifiers known as biologic agents, in particular the anti-TNFα agents (etanercept, infliximab, adalimumab), which directly inhibit the action of pro-inflammatory mediators, has revolutionized the treatment and the expected outcome of JIA. This article highlights treatment indications of anti-TNFα drugs and their more frequent side effects in JIA patients.

Torticollis as the Presenting Sign of Cervical Spondylodiscitis. - Pizzol, Antonio; Bramuzzo, Matteo; Pillon, Roberto; Taddio, Andrea; Barbi, Egidio (Pediatr Emerg Care, 2016)
Acquired torticollis is a common clinical finding in children evaluated in the pediatric emergency department. It may be the presentation symptom of different illnesses, such as trauma, muscle contraction, infections, or malignancies, and an accurate differential diagnosis is required to correctly identify the cause and choose the right treatment. Spondylodiscitis is a low-grade bacterial infection that involves intervertebral disks and the adjacent vertebral bodies. Spondylodiscitis of the cervical spine is unusual and may be a rare cause of torticollis. We report the case of a 4-year-old male patient admitted to the emergency department for a 5-day history of painful torticollis. Blood tests showed an elevated erythrocyte sedimentation rate. The radiograph of the cervical spine showed a thin fifth cervical soma. The magnetic resonance imaging of cervical spine showed the alteration of cervical vertebral bodies and intervertebral disks, suggesting the diagnosis of cervical spondylodiscitis. The patient recovered after endovenous antibiotic treatment. We suggest that cervical spondylodiscitis should be suspected and investigated by means of an magnetic resonance imaging in every case of unexplained torticollis with persisting symptoms.

Delayed reactivation of chronic infantile neurologic, cutaneous, articular syndrome (CINCA) in a patient with somatic mosaicism of CIAS1/NLRP3 gene after withdrawal of anti-IL-1 beta therapy. - Paloni, Giulia; Pastore, Serena; Tommasini, Alberto; Lepore, Loredana; Taddio, Andrea (Clin Exp Rheumatol, 2015)
Keywords: Antibodies, Monoclonal; Carrier Proteins; Cryopyrin-Associated Periodic Syndromes; Drug Administration Schedule; Female; Genetic Predisposition to Disease; Humans; Immunosuppressive Agents; Interleukin 1 Receptor Antagonist Protein; Interleukin-1beta; Mosaicism; Phenotype; Recurrence; Remission Induction; Time Factors; Treatment Outcome; Young Adult

Different presentations of mevalonate kinase deficiency: a case series. - De Pieri, Carlo; Taddio, Andrea; Insalaco, Antonella; Barbi, Egidio; Lepore, Loredana; Ventura, Alessandro; Tommasini, Alberto (Clin Exp Rheumatol, 2015)
OBJECTIVES: We aimed to raise awareness among paediatricians and physicians about this often misunderstood condition. METHODS: We discussed the clinical profiles associated with late or wrong diagnosis of mevalonate kinase deficency (MKD) in a single centre case series. RESULTS: We analysed the most common challenges and pitfalls that a clinician might face during the diagnostic process. Five main clinical profiles were characterised. CONCLUSIONS: We propose a new perspective on MKD, suggesting that the presentation of this disease can vary from patient to patient.
Keywords: Age Factors; Bacterial Infections; Child; Child, Preschool; Diagnosis, Differential; Diagnostic Errors; Female; Genetic Predisposition to Disease; Humans; Infant; Inflammatory Bowel Diseases; Male; Mevalonate Kinase Deficiency; Phenotype; Predictive Value of Tests; Recurrence; Risk Factors; Sepsis; Vasculitis; Young Adult

Failure of interferon-γ pre-treated mesenchymal stem cell treatment in a patient with Crohn's disease. - Taddio, Andrea; Tommasini, Alberto; Valencic, Erica; Biagi, Ettore; Decorti, Giuliana; De Iudicibus, Sara; Cuzzoni, Eva; Gaipa, Giuseppe; Badolato, Raffaela; Prandini, Alberto; Biondi, Andrea; Ventura, Alessandro (World J Gastroenterol, 2015)
Mesenchymal stem cells (MSC) are cells of stromal origin which exhibit unlimited self-renewal capacity and pluripotency in vitro. It has recently been observed that MSC may also exert a profound immunosuppressive and anti-inflammatory effect both in vitro and in vivo with consequent potential use in autoimmune disorders. We present the case of a patient suffering from childhood-onset, multidrug resistant and steroid-dependent Crohn's disease who underwent systemic infusions of MSC, which led to a temporary reduction in CCR4, CCR7 and CXCR4 expression by T-cells, and a temporary decrease in switched memory B-cells, In addition, following MSC infusion, lower doses of steroids were needed to inhibit proliferation of the patient's peripheral blood mononuclear cells. Despite these changes, no significant clinical benefit was observed, and the patient required rescue therapy with infliximab and subsequent autologous hematopoietic stem cell transplantation. The results of biological and in vitro observations after MSC use and the clinical effects of infusion are discussed, and a brief description is provided of previous data on MSC-based therapy in autoimmune disorders.

Fever tree revisited: From malaria to autoinflammatory diseases. - Pastore, Serena; Vuch, Josef; Bianco, Anna Monica; Taddio, Andrea; Tommasini, Alberto (World J Clin Pediatr, 2015)
Over the centuries the idea of recurrent fevers has mainly been associated with malaria, but many other fevers, such as typhoid and diphtheria were cause for concern. It is only in recent times, with the more severe forms of fever from infectious origin becoming less frequent or a cause for worry that we started noticing recurrent fevers without any clear infectious cause, being described as having a pathogenesis of autoinflammatory nature. The use of molecular examinations in many cases can allow a diagnosis where the cause is monogenic. In other cases, however the pathogenesis is likely to be multifactorial and the diagnostic-therapeutic approach is strictly clinical. The old fever tree paradigm developed to describe fevers caused by malaria has been revisited here to describe today's periodic fevers from the periodic fever adenitis pharyngitis aphthae syndrome to the more rare autoinflammatory diseases. This model may allow us to place cases that are yet to be identified which are likely to be of multifactorial origin.

Genetic determinants for methotrexate response in juvenile idiopathic arthritis. - Pastore, Serena; Stocco, Gabriele; Favretto, Diego; De Iudicibus, Sara; Taddio, Andrea; d'Adamo, Pio; Malusà, Noelia; Addobbati, Riccardo; Decorti, Giuliana; Lepore, Loredana; Ventura, Alessandro (Front Pharmacol, 2015)
Juvenile idiopathic arthritis (JIAs) is the most common chronic rheumatic disease of childhood and is an important cause of disability. The folic acid analog methotrexate is the first choice disease-modifying anti-rheumatic drug in this disease, however, 35-45% of patients fail to respond. Molecular elements, such as variants in genes of pharmacological relevance, influencing response to methotrexate in JIA, would be important to individualize treatment strategies. Several studies have evaluated the effects of candidate genetic variants in the complex pathway of genes involved in methotrexate pharmacodynamics and pharmacokinetics, however, results are still contrasting and no definitive genetic marker of methotrexate response useful for the clinician to tailor therapy of children with JIA has been identified. Recently, genome-wide approaches have been applied, identifying new potential biological processes involved in methotrexate response in JIA such as TGF-beta signaling and calcium channels. If these genomic results are properly validated and integrated with innovative analyses comprising deep sequencing, epigenetics, and pharmacokinetics, they will greatly contribute to personalize therapy with methotrexate in children with JIA.

Genetic profiling of autoinflammatory disorders in patients with periodic fever: a prospective study. - De Pieri, Carlo; Vuch, Josef; De Martino, Eleonora; Bianco, Anna M; Ronfani, Luca; Athanasakis, Emmanouil; Bortot, Barbara; Crovella, Sergio; Taddio, Andrea; Severini, Giovanni M; Tommasini, Alberto (Pediatr Rheumatol Online J, 2015)
BACKGROUND: Periodic fever syndromes (PFS) are an emerging group of autoinflammatory disorders. Clinical overlap exists and multiple genetic analyses may be needed to assist diagnosis. We evaluated the diagnostic value of a 5-gene sequencing panel (5GP) in patients with undiagnosed PFS. METHODS: Simultaneous double strand Sanger sequencing of MEFV, MVK, TNFRSF1A, NLRP3, NLRP12 genes was performed in 42 patients with unexplained PFS. Clinical features were correlated with genetic results. RESULTS: None of 42 patients analyzed displayed a causative genotype. However, single or multiple genetic variants of uncertain significance were detected in 24 subjects. Only in 5 subjects a definite diagnosis was made by taking into account both genetic and clinical data (2 TRAPS syndrome; 2 FMF; 1 FCAS). Statistical analysis showed that patients carrying genetic variants in one or more of the five selected genes displayed a significantly lower response to glucocorticoids compared with subjects who had completely negative genetic results. CONCLUSIONS: The sequencing of multiple genes is of little help in the diagnostics of PFS and can often lead to results of uncertain interpretation, thus the clinically driven sequencing of single genes should remain the recommended approach. However, the presence of single or multiple genetic variants of uncertain significance, even if not allowing any specific diagnosis, correlated with a poorer response to glucocorticoids, possibly indicating a multifactorial subgroup of PFS with differential response to pharmacological treatment.
Keywords: Adolescent; Carrier Proteins; Child; Cryopyrin-Associated Periodic Syndromes; Cytoskeletal Proteins; Familial Mediterranean Fever; Female; Fever; Gene Expression Profiling; Genotype; Hereditary Autoinflammatory Diseases; Humans; Intracellular Signaling Peptides and Proteins; Logistic Models; Male; Mutation; Phosphotransferases (Alcohol Group Acceptor); Prospective Studies; Receptors, Tumor Necrosis Factor, Type I; Syndrome

More than (Double) Bubble. - Ferrara, Giovanna; Stampalija, Tamara; Codrich, Daniela; Simionato, Cristina; Taddio, Andrea; Travan, Laura (J Pediatr, 2015)
Keywords: Amniotic Fluid; Duodenum; Female; Humans; Infant; Infant, Newborn; Polyhydramnios; Pregnancy; Pregnancy Trimester, Third; Prenatal Diagnosis; Ultrasonography, Prenatal

Nasal irrigation with saline solution significantly improves oxygen saturation in infants with bronchiolitis. - Schreiber, Silvana; Ronfani, Luca; Ghirardo, Sergio; Minen, Federico; Taddio, Andrea; Jaber, Mohamad; Rizzello, Elisa; Barbi, Egidio (Acta Paediatr, 2015)
AIM: Published guidelines do not recommend nasal irrigation in bronchiolitis, but it is common practice in Italy, despite a lack of data on its benefits or adverse effects. This single-blind, multicentre, randomised controlled trial compared nasal irrigation using either isotonic 0.9% sodium chloride or hypertonic 3% sodium chloride with simple supportive care in infants with bronchiolitis. METHOD: We randomly assigned 133 Infants up one year of age, who were admitted to the emergency department with bronchiolitis and an oxygen saturation (SpO2) of between 88-94%, to the isotonic (n=47), hypertonic (n=44) or standard care (n=42) groups. Variations in SpO2 and the wheeze, air exchange, respiratory rate, muscle use (WARM) respiratory distress score were recorded at zero, five, 15, 20 and 50 minutes. RESULTS: Five minutes after the intervention, the median SpO2 value (95%) in the isotonic group was higher than both the hypertonic (94%) and the standard care (93%) groups. The differences between the isotonic and standard treatment groups were statistically significant at each time point, while the hypertonic group only reached significantly higher values after 50 minutes. However, the WARM score did not improve. CONCLUSION: A single nasal irrigation with saline solution significantly improved oxygen saturation in infants with bronchiolitis. This article is protected by copyright. All rights reserved.

Normal saline flushes performed once daily maintain peripheral intravenous catheter patency: a randomised controlled trial. - Schreiber, Silvana; Zanchi, Chiara; Ronfani, Luca; Delise, Anna; Corbelli, Alessandra; Bortoluzzi, Rosamaria; Taddio, Andrea; Barbi, Egidio (Arch Dis Child, 2015)
OBJECTIVE: Recent evidence supports the use of normal saline flushes in place of heparin to maintain the patency of peripheral intravenous locks (IVLs); however, there are no data regarding the recommended flush frequency. STUDY DESIGN: This was an open, non-inferiority, randomised controlled trial. Children with IVLs, aged 1-17 years, were randomly assigned to receive saline flushing every 12 h (group A) or every 24 h (group B). The main outcome was the maintenance of catheter patency. RESULTS: Four hundred patients were randomised; 198 subjects were analysed in the 12 h group and 199 in the 24 h group (three patients were lost at follow-up). Occlusion occurred in 15 children (7.6%) in group A versus 9 (4.5%) in group B (p=0.21). The difference in catheter patency was +3.1% in favour of the 24 h group (95% CI -1.6% to 7.7%), showing the non-inferiority of the 24 h procedure (the non-inferiority margin was set at -4%). Catheter-related complications were not different between the two groups (12.1% in group A vs 9.5% in group B; p=0.42). CONCLUSIONS: A flushing procedure with one flush per day allows maintenance of catheter patency without an increase in catheter-related complications. We propose a simplification of the flushing procedure with only one flush per day, thereby reducing costs (materials use and nursing time), labour and unnecessary manipulation of the catheters which can cause distress in younger children and their parents. TRIAL REGISTRATION NUMBER: The study is registered in the international database ClinicalTrial.gov under registration number NCT02221024.
Keywords: Adolescent; Catheterization, Peripheral; Catheters, Indwelling; Child; Child, Preschool; Equipment Failure; Female; Humans; Infant; Male; Outcome Assessment (Health Care); Risk Assessment; Sodium Chloride; Therapeutic Irrigation

Orofacial granulomatosis in children: think about Crohn's disease. - Lazzerini, Marzia; Martelossi, Stefano; Cont, Gabriele; Bersanini, Chiara; Ventura, Giovanna; Fontana, Massimo; Zuin, Giovanna; Ventura, Alessandro; Taddio, Andrea (Dig Liver Dis, 2015)
BACKGROUND: The term orofacial granulomatosis is conventionally used to describe patients with granulomatous lesions affecting the orofacial tissues, in absence of intestinal lesions. Lip swelling and facial swelling are the most common clinical signs. Despite the fact that histologically it is not distinguishable from Crohn's disease, and that both diseases have a chronic/recurrent course, the relationship between orofacial granulomatosis and Crohn's disease is still debated. METHODS: Herein we present five cases of orofacial granulomatosis. RESULTS: All patients presented concomitant Crohn's disease, supporting the hypothesis that orofacial granulomatosis and Crohn's disease may be one single disease. Thalidomide was effective in inducing remission of oral and intestinal symptoms in all five cases and could be considered a valid treatment opportunity for these patients. CONCLUSIONS: Orofacial granulomatosis and Crohn's disease may be part of the same disease; both may respond to thalidomide.
Keywords: Adolescent; Biopsy; Child; Colonoscopy; Crohn Disease; Diagnosis, Differential; Female; Granulomatosis, Orofacial; Humans; Immunosuppressive Agents; Male; Thalidomide

Three cases of Bartonella quintana infection in children. - Magnolato, Andrea; Pederiva, Federica; Spagnut, Giulia; Maschio, Massimo; Ventura, Alessandro; Taddio, Andrea (Pediatr Infect Dis J, 2015)
We present 3 children affected by B. quintana infection treated at the IRCCS Burlo Garofolo of Trieste between March and April 2013. B. quintana infection is rare but it should be suspected in patients with fever and lymphadenopathy who do not respond to conventional antibiotic treatment. All patients had a complete recovery without sequelae or relapses.

Clinical significance of hyper-IgA in a paediatric laboratory series. - Copetti, Valentina; Pastore, Serena; De Pieri, Carlo; Radillo, Oriano; Taddio, Andrea; Ventura, Alessandro; Tommasini, Alberto (Arch Dis Child, 2014)
The causes of extremely elevated IgA, whether isolated or associated with an increase in other classes of immunoglobulin, are poorly defined in paediatrics. We reviewed the diagnostic significance of very high IgA levels (greater than 3 SD above the mean for age) in a cohort of patients referred to a tertiary care children's hospital. Hyper-IgA was found in 91 of 6364 subjects (1.4%) and in 68 cases was not associated with an increased IgG and/or IgM level. Most subjects with hyper-IgA (73.5%) had a severe immune defect, a chronic rheumatic disease or inflammatory bowel disease, while these conditions were very rare in a control group with normal IgA values (8%). Although our results may in part reflect the experience of a tertiary care centre, we suggest that hyper-IgA in children should always arouse suspicion of a serious disease.
Keywords: Adolescent; Child; Child, Preschool; Female; Hospitals, Pediatric; Humans; Hypergammaglobulinemia; Immunoglobulin A; Infant; Italy; Male; Tertiary Care Centers

A comparison of three scales for measuring pain in children with cognitive impairment. - Massaro, Marta; Ronfani, Luca; Ferrara, Giovanna; Badina, Laura; Giorgi, Rita; D'Osualdo, Flavio; Taddio, Andrea; Barbi, Egidio (Acta Paediatr, 2014)
AIM: Pain is a neglected problem in children with cognitive impairments, and few studies compare the clinical use of specific pain scales. We compared the Non-Communicating Children's Pain Checklist Postoperative Version (NCCPC-PV), the Echelle Douleur Enfant San Salvador (DESS) and the Children's Hospital of Eastern Ontario Pain Scale (CHEOPS). The first two were developed for children with cognitive impairment, and the third is a more general pain scale. METHODS: Two external observers and the child's caregiver assessed 40 children with cognitive impairment for pain levels. We assessed inter-rater agreement, correlation, dependence on knowledge of the child's behaviour, simplicity and adequacy in pain rating according to the caregiver for all three scales. RESULTS: The correlation between the NCCPC-PV and the DESS was strong (Spearman correlation coefficient = 0.76) and better than between each scale and the CHEOPS. Although the DESS showed better inter-rater agreement, it was more dependent on familiarity with the child and was judged more difficult to use by all observers. The NCCPC-PV was the easiest use and the most appropriate for rating the child's pain. CONCLUSION: The NCCPC-PV was the easiest to use for pain assessment in cognitively impaired children and should be adopted in clinical settings.

Procedural sedation for intra-articular corticosteroid injections in juvenile idiopathic arthritis (JIA) should be a standard of care. - Pastore, Serena; Gortani, Giulia; Taddio, Andrea; Barbi, Egidio (Eur J Pediatr, 2014)
Keywords: Arthritis, Juvenile; Conscious Sedation; Female; Glucocorticoids; Humans; Male; Pain; Patient Preference

Serum amyloid protein A concentration in cryopyrin-associated periodic syndromes patients treated with interleukin-1 beta antagonist. - Pastore, Serena; Paloni, Giulia; Caorsi, Roberta; Ronfani, Luca; Taddio, Andrea; Lepore, Loredana (Clin Exp Rheumatol, 2014)
OBJECTIVES: Cryopyrin-associated periodic syndromes (CAPS) are a group of chronic, relapsing autoinflammatory disorders which may be complicated by systemic AA amyloidosis. The aim of our study was to evaluate serum amyloid protein A (SAA) level in CAPS patients treated with Interleukin-1beta (IL-1β) antagonist and to correlate its level with treatment response. METHODS: All patients of CAPS Italian Register treated with IL-1β inhibitor were enrolled. SAA levels before starting therapy, and at last visit were evaluated. Patients were then divided in complete responders and partial responders. RESULTS: Twenty-five patients were enrolled. SAA level before starting therapy was increased (median 118.5 mg/L, IQR 96.4-252.8; normal value <6.4 mg/L), while at last visit SAA was significantly reduced (median 4.3 mg/L, IQR 2.3-12.7) (p<0.001). However 12 patients still presented SAA levels beyond normal range, 10/25 patients (40%) showed a complete response to treatment. Conversely, 15 patients presented only a partial response, of which 12 for increased SAA value and 3 for increased CRP value. Patients with partial response had SAA values significantly higher than patients with complete response (median 12.6 mg/L; IQR 8.3-20.0 vs. 2.7 mg/L; IQR 1.6-4.1, p<0.001). CONCLUSIONS: Our results confirm the long term efficacy of anti IL-1β treatment in CAPS and the decrease of SAA levels; however 48% of patients still presented SAA elevation despite treatment. The real risk of these patients in developing amyloidosis is not clear but the persistent increase of SAA needs a close follow-up.
Keywords: Adolescent; Adult; Amyloidosis; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Drug Monitoring; Female; Humans; Immunosuppressive Agents; Interleukin-1beta; Male; Middle Aged; Serum Amyloid A Protein; Treatment Outcome; Young Adult

Acute febrile cholestatic jaundice in children: keep in mind Kawasaki disease. - Taddio, Andrea; Pellegrin, Maria Chiara; Centenari, Chiara; Filippeschi, Irene Pellegrini; Ventura, Alessandro; Maggiore, Giuseppe (J Pediatr Gastroenterol Nutr, 2012)
Kawasaki disease (KD) is characterized by persistent fever in addition to 4 of 5 signs of mucocutaneous inflammation. Although gastrointestinal involvement does not belong to the classic diagnostic criteria, it has been often associated with KD onset. We reviewed patients who were admitted for febrile cholestatic jaundice between 2003 and 2010 in 2 tertiary pediatric care centers. KD was the second most frequent cause (21%) after viral infections. Considering the relative high frequency of this condition, a high index of suspicion of KD should be maintained in patients presenting with febrile cholestatic jaundice.
Keywords: Child; Child, Preschool; Diagnosis, Differential; Female; Fever; Humans; Infant; Jaundice, Obstructive; Male; Mucocutaneous Lymph Node Syndrome; Virus Diseases

Dealing with abdominal pain in children affected by systemic lupus erythematosus. - Taddio, Andrea; Rosé, Carlos; Lepore, Loredana; Ventura, Alessandro (Semin Arthritis Rheum, 2012)
Keywords: Abdominal Pain; Female; Humans; Lupus Erythematosus, Systemic; Male

From bone marrow transplantation to cellular therapies: possible therapeutic strategies in managing autoimmune disorders. - Taddio, Andrea; Biondi, Andrea; Piscianz, Elisa; Valencic, Erica; Biagi, Ettore; Badolato, Raffaele (Curr Pharm Des, 2012)
Chronic inflammatory disorders occurring in childhood represent a serious therapeutic challenge. However, available therapies seem not to be targeted on the pathogenic mechanism of the disease and are often not actively affecting the natural history of the disease. Emerging treatments might be of some benefit to many patients who did not respond to conventional therapeutic options. Biological therapies with monoclonal antibodies and other recombinant proteins have been introduced in clinical practice. At the same time, mesenchymal stromal cells (MSC) have gained attention as a savage treatment in patients subjected to hematopoietic stem cell transplantation who develop severe graft versus host disease (GvHD); in addition, recent reports from clinical trials on larger cohorts of patients support their use as second-line treatment after failure of corticosteroid treatment. For analogy, they have been proposed for the treatment of intractable autoimmune disorders. Hematopoietic stem cell transplantation (HSCT) has been shown to be effective for treatment of rheumatic disorder cases that were resistant to traditional therapies especially if combined with cell manipulation techniques, such as selection of regulatory T cell and depletion of harmful lymphocytes. We herein present the rationale of different strategies, the preliminary data obtained in clinical trials, unsolved problems and possible next developments of novel treatment protocols of autoimmune disorders.
Keywords: Autoimmune Diseases; Bone Marrow Transplantation; Child; Chronic Disease; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Inflammation; Lymphocytes; Mesenchymal Stem Cell Transplantation; T-Lymphocytes, Regulatory; Treatment Outcome

Acute cardiac valvular involvement in Kawasaki Disease. - Pellegrin, Maria Chiara; Taddio, Andrea; Lepore, Loredana (Clin Exp Rheumatol, 2011)
Keywords: Adrenal Cortex Hormones; Child, Preschool; Female; Heart Valve Diseases; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant; Male; Mucocutaneous Lymph Node Syndrome; Treatment Outcome

Childhood chronic anterior uveitis associated with vernal keratoconjunctivitis (VKC): successful treatment with topical tacrolimus. Case series. - Taddio, Andrea; Cimaz, Rolando; Caputo, Roberto; de Libero, Cinzia; Di Grande, Laura; Simonini, Gabriele; Mori, Francesca; Novembre, Elio; Pucci, Neri (Pediatr Rheumatol Online J, 2011)
Uveitis treatment involves topical corticosteroids along with cycloplegic-mydriatics. Particularly severe cases may require systemic corticosteroids and immunosuppressive drugs. Vernal keratoconjunctivitis (VKC) treatment consists of a brief period of topical corticosteroids and/or cyclosporine. In patients refractory to traditional treatment, the use of 0.1% topical ophtalmic FK- 506 (tacrolimus) ointment has been occasionally reported.This is the first report of the coexistence of uveitis and VKC. The documented response to topical tacrolimus eyedrop of uveitis and VKC is also of interest, in particular since to our knowledge there are no published reports on its clinical use in uveitis.

Clinical heterogeneity and diagnostic delay of autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy syndrome. - Mazza, Cinzia; Buzi, Fabio; Ortolani, Federica; Vitali, Alberto; Notarangelo, Lucia D; Weber, Giovanna; Bacchetta, Rosa; Soresina, Annarosa; Lougaris, Vassilios; Greggio, Nella A; Taddio, Andrea; Pasic, Srdjan; et al. (Clin Immunol, 2011)
Autoimmune polyendocrinopathy-candidiasis-ectodermal dystrophy (APECED) is a rare autosomal recessive organ-specific autoimmune disorder that is characterized by a variable combination of (i) chronic mucocutaneous candidiasis, (ii) polyendocrinopathy and/or hepatitis and (iii) dystrophy of the dental enamel and nails. We analyzed the AIRE (autoimmune regulator) gene in subjects who presented any symptom that has been associated with APECED, including candidiasis and autoimmune endocrinopathy. We observed that 83.3% of patients presented at least two of the three typical manifestations of APECED, while the remaining 16.7% of patients showed other signs of the disease. Analysis of the genetic diagnosis of these subjects revealed that a considerable delay occurs in the majority of patients between the appearance of symptoms and the diagnosis. Overall, the mean diagnostic delay in our patients was 10.2 years. These results suggest that molecular analysis of AIRE should be performed in patients with relapsing mucocutaneous candidiasis for early identification of APECED.
Keywords: Adolescent; Adult; Child; Child, Preschool; Heterozygote; Homozygote; Humans; Middle Aged; Mutation; Polyendocrinopathies, Autoimmune; Time Factors; Young Adult

Gastroesophageal reflux disease at any cost: a dangerous paediatric attitude. - Taddio, Andrea; Bersanini, Chiara; Basile, Lucio; Fontana, Massimo; Ventura, Alessandro (Acta Paediatr, 2011)
Keywords: Diagnostic Errors; Gastroesophageal Reflux; Humans; Inappropriate Prescribing; Infant; Infant, Newborn; Male; Proton Pump Inhibitors; Spasms, Infantile

The resurgence of rheumatic fever in a developed country area: the role of echocardiography. - Pastore, Serena; De Cunto, Angela; Benettoni, Alessandra; Berton, Emanuela; Taddio, Andrea; Lepore, Loredana (Rheumatology (Oxford), 2011)
OBJECTIVES: The annual incidence of ARF ranges from 5 to 51/100, 000 population worldwide in the 5- to 15-year age group. In the past, there was a decline in the incidence of ARF; however, focal outbreaks have been reported. This study evaluated the incidence of ARF in 2007-08 in a region of a developed country compared with the previous decade. METHODS: A retrospective review of all admission records for ARF in Trieste between January 2007 and December 2008 was undertaken. The diagnosis of ARF was established by the Jones criteria according to the 1992 revision. RESULTS: Between January 2007 and December 2008: 13 cases of ARF were recorded, 11 females and 2 males. The estimated incidence was 23 and 27/100, 000 population new cases each year, respectively, in the 5- to 15-year age group. Migratory polyarthritis occurred in 6/13, chorea in 7/13 and clinical carditis in 5/13 cases. Five out of 13 patients had only echocardiographic abnormalities, with no clinical cardiac manifestations. Another two patients did not fulfil diagnostic criteria for ARF, presenting with only three minor criteria, but they revealed silent carditis at echocardiography evaluation. During the follow-up, in one case the carditis receded and in the other it significantly improved. CONCLUSIONS: Our experience underlines that ARF has not yet disappeared in industrialized countries. We observed a high incidence of chorea, always associated with mild carditis. Echocardiographic assessment should be routinely performed in all patients with suspected ARF in order to identify those subclinical cases of valvulitis that would otherwise pass undiagnosed without receiving proper prophylaxis.
Keywords: Adolescent; Child; Child, Preschool; Chorea; Developed Countries; Diagnosis, Differential; Echocardiography; Female; Humans; Italy; Male; Myocarditis; Retrospective Studies; Rheumatic Fever

Usefulness of wireless capsule endoscopy for detecting inflammatory bowel disease in children presenting with arthropathy. - Taddio, Andrea; Simonini, Gabriele; Lionetti, Paolo; Lepore, Loredana; Martelossi, Stefano; Ventura, Alessandro; Cimaz, Rolando (Eur J Pediatr, 2011)
Inflammatory bowel disease (IBD) is a cause of chronic intestinal inflammation in children. In a subset of patients affected by IBD, arthropathy may be the leading presenting sign. In the past years, remarkable advances in gastrointestinal endoscopy techniques have been achieved; recently, the development of capsule endoscopy (CE) provided a non-invasive method for the complete endoscopic evaluation, including small bowel assessment. We report three children suffering from IBD but presenting with articular complaints in whom CE was a useful tool for detecting gut inflammation. Patients were investigated with the wireless CE: PillCam SB2 (Given Imaging, Yoqneam, Israel) capsule, the second-generation capsule, was used in our paediatric patients. Three patients were initially evaluated for arthropathy. Enteropathic arthritis was suspected for gastrointestinal symptoms and/or persistence of inflammatory markers elevation. In one of these children, conventional endoscopy was refused by parents, while in the other two children, CE was proposed as first-line diagnostic tool. In all patients, CE revealed to be safe and provided information that led to diagnosis. Paediatric rheumatologists should consider CE as a valid, non-invasive tool, eventually first level diagnostic approach in order to evaluate the presence of IBD in children presenting with chronic articular complaints.
Keywords: Adolescent; Arthritis, Juvenile; Capsule Endoscopy; Child; Colitis, Ulcerative; Colon; Crohn Disease; Diagnosis, Differential; Follow-Up Studies; Humans; Inflammatory Bowel Diseases; Intestine, Small; Male; Predictive Value of Tests; Sensitivity and Specificity; Severity of Illness Index; Treatment Outcome

Defective FOXP3 expression in patients with acute Kawasaki disease and restoration by intravenous immunoglobulin therapy. - Olivito, Biagio; Taddio, Andrea; Simonini, Gabriele; Massai, Cristina; Ciullini, Sara; Gambineri, Eleonora; de Martino, Maurizio; Azzari, Chiara; Cimaz, Rolando (Clin Exp Rheumatol, 2010)
OBJECTIVES: The aims of this study were: 1) to investigate forkhead box P3 (FOXP3) expression in patients with Kawasaki disease (KD), exploring possible differences during the acute phase and after defervescence; 2) to evaluate a possible association of the FOXP3 single nucleotide polymorphism (SNP) 543 (SNP ID: rs2232367) with KD. METHODS: FOXP3 expression was evaluated on 8 children with KD and 15 healthy children by flow cytometry and Real-Time polymerase chain reaction (RT-PCR). FOXP3 SNP 543 was genotyped by denaturing high-performance liquid chromatography (DHPLC) and sequencing on DNA samples from 58 additional children with KD and 114 healthy donors. RESULTS: The frequencies of CD4+CD25 +FOXP3+ regulatory T cells were significantly (p=0.0002) lower during the acute phase of KD than in sex- and age-matched healthy donors (median % + SD: 4.8+/-1.3 vs. 7.7+/-1.7) and a similar tendency was revealed for FOXP3 mRNA transcripts (p<0.0001). FOXP3 expression increased significantly, at both protein and mRNA levels, after intravenous immunoglobulin (IVIG) therapy treatment and achieving complete remission of disease (at least 48 hrs; median 9.5 days, range 2-30). Of the 58 patients screened, only one female subject (1.7%) carried the presence of 543 SNP in heterozygosis (C>T; for a total of 1 allele out of 88), with no difference between KD patients and controls (0.0%, 0/203 alleles). CONCLUSIONS: Our data reinforce the notion of an impaired immunoregulation in KD, suggesting also a role of IVIG treatment in modifying the Treg compartment. FOXP3 SNP 543 does not seem to be involved in susceptibility to KD in Italian children.
Keywords: Acute Disease; Child; Child, Preschool; Female; Flow Cytometry; Forkhead Transcription Factors; Genotype; Humans; Immunoglobulins, Intravenous; Infant; Italy; Male; Mucocutaneous Lymph Node Syndrome; Polymorphism, Single Nucleotide; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; T-Lymphocytes, Regulatory

The universe of immune deficiencies in Crohn's disease: a new viewpoint for an old disease? - Tommasini, Alberto; Pirrone, Angela; Palla, Gabriella; Taddio, Andrea; Martelossi, Stefano; Crovella, Sergio; Ventura, Alessandro (Scand J Gastroenterol, 2010)
Crohn's disease (CD) is generally considered a multifactorial disorder, since different genetic and environmental factors are thought to play a role in its pathogenesis. Recently, genome wide linkage studies allowed to identify the association of several loci with the increased risk of CD, although it is still unclear how they interact with environmental factors in causing the disease. The fact that many CD-risk-related genes are involved in the function of phagocytes seems in agreement with the well known role of these cells in CD histopathology. Functional defects in cytokine production or in clearance of bacteria in CD patients have recently been reported. Growing evidence that CD could arise from primary phagocyte immunodeficiency is also coming from the study of cases with early onset in infancy. We review such evidences starting from selected cases and discuss the clinical implications of these findings.
Keywords: Biological Markers; Crohn Disease; Cytokines; Evidence-Based Medicine; Granulomatous Disease, Chronic; Hematopoietic Stem Cell Transplantation; Humans; Immunosuppressive Agents; Phagocytes; Treatment Outcome; Wiskott-Aldrich Syndrome

Use of ketamine continuous infusion for pediatric sedation in septic shock. - Barbi, Egidio; Rizzello, Elisa; Taddio, Andrea (Pediatr Emerg Care, 2010)
Keywords: Anesthetics, Dissociative; Child; Conscious Sedation; Humans; Infusions, Intravenous; Ketamine; Male; Shock, Septic